Critical revision of the alleged delayed dental eruption in South American “ungulates” - Kramarz, Alejandro Gustavo (2013)
The endemic South American “ungulates” (SANU) were traditionally assumed to be a monophyletic offshoot of the Granorder Ungulata, but the current reorganization of the extant ungulates in Laurasiatheria and Afrotheria (based on molecular data) leaved them in an undetermined systematic position. The delayed dental eruption versus cranial growth was proposed as a hard-tissue synapomorphy of Afrotheria. In a recent paper, at least some endemic SANU (Notoungulata, Astrapotheria, and possibly Pyrotheria) were interpreted as allied to Afrotheres by having a late replacement of deciduous cheek teeth. This statement was based on: (1) the usual occurrence within these groups of individuals with deciduous and permanent teeth; (2) the individual size (estimated comparing the length/width ratio of cheek teeth) of specimens with permanent premolars erupted is indistinguishable from that of specimens with deciduous premolars (putative juveniles), and (3) the retention of at least dP1–dP3 in adult specimens of Parastrapotherium (Astrapotheria). Herein we critically examine the presumed existence of delayed dental eruption in astrapotheres, pyrotheres and xenungulates and the assumptions on which it was based. The alleged evidences supporting the occurrence of delayed dental eruption in SANU arise from misinterpreted information from the literature and conceptual mistakes (i.e. delayed dental eruption versus cranial growth was confused with delayed replacement of premolars versus molar eruption). Based on examination of at-hand specimens, we found that there is no evidence for a delayed premolar replacement relative to the eruption of the molars in astrapotheres, pyrotheres, and xenungulates. A delayed dental eruption in relation to jaw growth does not occur at least in Astrapotherium magnum. Although a very recent study proposed close relationships among afrotheres and at least notoungulates and xenungulates, a more complete analysis is still needed to elucidate the evolutionary relationships of astrapotheres and pyrotheres.